Stress-sensitivity of carbon nanotube-grafted-carbon fiber incorporated cement-based composites. (1st April 2023) - Liu, Xiaoyan; Wang, Gangao; yu, Jinyao; Liu, Ruidan; Lyu, Kai; Zuo, Junqing; Shah, Surendra P.
Abstract: The article studied the stress-sensitivity of carbon nanotube-grafted-carbon fiber incorporated cement-based composites under temperature and humidity, and further investigated the piezoresistive stability of the composite embedded in the concrete as a sensor. This study employed hydrothermal synthesis to graft carbon nanotubes (CNTs) onto the surface of carbon fibers (CFs) to prepare CNT-grafted-CF reinforced composites (CNT-CF). CNT-CF was added to cement to prepare CNT-CF incorporated cement-based composites (CNT-CF/CC). The connection of the conductive network and the micromorphology of CNT-CF in the cement matrix were characterized by scanning electron microscope (SEM). Four-electrode method was used to investigate the electrical conductivity. Cyclic loading test was performed to test the intelligent performance of CNT-CF/CC under different temperatures and humidity. The results demonstrated that compared with CFs, CNT-CF was surrounded by more hydration products. The CNTs on the surface of CFs increased the roughness of CFs. SEM images revealed that CNT-CF was more firmly bonded with the cement matrix. Moreover, CNT-CF/CC had better electrical and sensitive properties. Thus, it was explored for the application in stress-sensors for monitoring the change of stress in concrete. The results showed that smart concrete prepared by embedded stress-sensors also exhibited sensitive piezoresistive effect. Highlights: Compared with CF/CC, the resistivity of CNT-CF/CC can be greatly reduced, and the adhesion of CNT-CF and cement significantly improved. Under the combined effect of load and temperature and load and humidity, CNT-CF/CC had better piezoresistive stability than CF/CC. Smart concrete embedded with CNT-CF/CC also exhibited stable piezoresistive effect. Under unit load, the relationships between temperatures and resistivity, and humidity and resistivity can be used to monitor changes in the internal stress of concrete.